Using active learning with smart board to enhance primary school students' higher order thinking skills in data handling - Abdullah, Abdul Halim (Horizon Research Publishing, 2020)
Data Handling is an important topic in the Mathematics Primary Curriculum as it brings the real world of seeing data to students. However, the assessments of PISA and TIMSS indicated that the level of Malaysian students' performance and Higher Order Thinking Skills (HOTS) in Data Handling is declining. Thus, this study was designed to develop active learning instructions using smart board (ALuSB programme) and to evaluate its effectiveness in enhancing HOTS among Malaysian students in Data Handling. The study was carried out in two stages; the design and development of ALuSB programme stage based on ADDIE model and the evaluation stage to see the enhancement of HOTS in Data Handling. The research design adopted for this study was a pre-test post-test quasi-experimental design using non-equivalent control group. Quantitative and qualitative data were collected for analyses. The quantitative data was analysed using One-way ANOVA to evaluate the mean differences between the treatment groups whereas a post hoc test was further used to determine precisely which mean differences were significant and visa-versa among all the three groups. Additionally, the qualitative data was analysed using thematic analysis. The findings in this study indicated that ALuSB programme has the potential to improve students' performance and HOTS in Data Handling. Students also demonstrated increase in their ability to carry out a procedure, differentiate and organise data, make judgments and create a table or graph, making the ALuSB programme suitable to be applied in schools as it can effectively help students to enhance their HOTS.